Determinants of Systematic Risk of State-Owned Enterprises in the Construction Sector Listed on the Indonesia Stock Exchange - Irni Yunita; Bayu Aji Prasetyo; Fajra Octrina (Budapest International Research and Critics University, 2022)
The business activities run by the State-Owned Enterprises (BUMN) in Indonesia significantly affect the development of the business world and society. The construction sector industry is one of the SOEs that has an influence in the growth process in Indonesia. This research is a study of financial ratios consisting of liquidity ratios, activity ratios, solvency ratios and profitability ratios as factors that influence systematic risk in stocks. This study will determine which factors or variables from financial ratios have the most dominant influence on systematic risk. The sampling technique used is purposive sampling with the criteria (1) Construction Sector BUMN Companies listed on the Indonesia Stock Exchange which have Persero and Tbk status (2) Construction sector BUMN companies that have complete financial reports and have complete data needed in the study. during the period 2016 to 2019 on the Indonesia Stock Exchange. This study uses annual report data from sixty-two construction companies listed on the Indonesia Stock Exchange for the period 2016 to 2019. A total of sixty-two companies can be used as populations and four are used as research samples. The method used for this research is panel data. The results that are known from this study are Current Ratio (CR), Total Asset Turnover (TATO), Debt-to-equity Ratio (DER), Return n Equity (ROE) variables partially have no effect on the stock beta variable. The variables Current Ratio (CR), Total Asset Turnover (TATO), Debt-to-equity Ratio (DER), Return on Equity (ROE) simultaneously have no effect on the stock beta variable.